Cobalt-catalyzed directed : ortho-methylation of arenes with methyl tosylate - Sun, Qiao (2020)
A cobalt-catalyzed directed ortho C-H methylation reaction of arenes has been achieved using readily available methyl tosylate as a methylating agent. An in situ-generated cobalt-N-heterocyclic carbene catalyst in combination with neopentylmagnesium bromide promotes the methylation at room temperature. The reaction is applicable to various substrates bearing nitrogen directing groups such as N-aryl imine, N-H imine, and 2-pyridyl groups. The present protocol also allows for facile introduction of a trideuteriomethyl group into arenes.